Human Soul in the Light of Czesław Stanisław Bartnik’s Universalistic Personalism - Miczyński, Jan (Verbum Vitae, 2022)
The article presents a contemporary understanding of the human soul according to Czesław Stanisław Bartnik (1929–2020), the founder of universalistic personalism. The term “soul” has been understood in many different ways throughout the history of human thought, hence it still raises confusion today. It is sometimes dismissed as too “religious” and replaced by the word “ego” or “person.” It seems that a successful attempt to link the history of human thought with a contemporary understanding of the person is Bartnik’s personalistic system. The article groups Bartnik’s thoughts on the “human soul” into four main blocks: personalistic reflection on the history of the concept of “soul”; place of the soul in the structure of the contemporary person (real being); clarification of the significance of the soul’s “function” in the inner and outer world of an individual; the existence of a “social person” and – in a sense – a “social soul” i.e., the spiritual self-awareness of society (although there is no single common soul for all people). The analysis leads to the following conclusions: the terms “soul” and “person” are not synonymous today; the meaning of “person” is broader than that of “soul,” however, the “person” does not displace the “soul.” Putting it positively, the soul together with the body constitutes human nature, and thanks to this nature, there is a metaphysical personal “self” (ontic ego) which can be described as a “spiritual soul” or “spirit” (whereby the metaphysical “self” is inseparable from the “soul”) Man as a person expresses himself through body and soul, as well as the metaphysical self (which is present in the consciousness). Because of its “spiritual soul,” a person is constantly in development, transcends reality and is moving towards its ultimate fulfilment in the Communion of the Divine Persons. This is done by making the right moral choices, in conjunction with the Person of Jesus Christ.